Relationship between physical activity, stress levels, and sleep quality in adolescents - Ni Kadek Ayu Bintang Luwita Dewi; Sayu Aryantari Putri Thanaya; I Putu Yudi Pramana Putra; Gede Parta Kinandana (Universitas Udayana dan Diaspora Taipei Medical University, 2024)
Background: Quality sleep is important for recovery, but adolescents often experience sleep disturbances during puberty. Low physical activity, such as playing online games, and stress from many tasks can reduce their sleep quality. This study aimed to determine whether there is a relationship between physical activity level and stress on sleep quality in adolescents. Methods: This research used observational analytics method with a cross-sectional design. The study used apurposive sampling of 232 people in junior high schools in Denpasar. The inclusion criteria were teenagers aged 16-17, while the exclusion criteria were respondents who smoked, drank alcoholic beverages, and took sleeping pills. Data were collected by measuring physical activity levels using the international physical activity questionnaire (IPAQ), stress using the depression anxiety and stress scale (DASS-21), and sleep quality using the Pittsburgh sleep quality index (PSQI). Results: Based on the results of the non-parametric analysis of Spearman Rho, it showed that there was a relationship between physical activity and sleep quality with a significance value of p = 0.001 (p <0.05) correlation coefficient (r = 0.464). There was a relationship between stress and sleep quality with a value of p = 0.001 (p <0.05) correlation coefficient (r = 0.671). Conclusion: Based on the results, it could be concluded that there was a relationship between physical activity level and sleep quality in adolescents. There was also a relationship between stress and sleep quality in adolescents.